2009
DOI: 10.1002/marc.200900496
|View full text |Cite
|
Sign up to set email alerts
|

Using Metallo‐Supramolecular Block Copolymers for the Synthesis of Higher Order Nanostructured Assemblies

Abstract: Many research groups have explored the properties and solution self-assembly of main chain metallo-supramolecular multiblock copolymers. Until recently, these metal complexes have been used to prepare mainly micelle type structures. However, the self-assembly of such copolymers has been exploited further to create more advanced architectures which utilize the reversible supramolecular linkage of their building blocks as a key component in their synthesis. Furthermore, the incorporation of multiple orthogonal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 119 publications
(148 reference statements)
0
47
0
1
Order By: Relevance
“…[2][3][4][5][6][7][8] Typical Janus particles were micro-or nano-sized particles composed of two hemispheres with distinct chemical or physical properties. [11][12][13][14][15][16][17] However, the difficulties in synthesizing Janus supramolecular polymers were enormous. 9,10 These unique properties also made Janus-type supramolecular polymers very promising in biomedical applications including mimicking primitive biological membranes, conguring into biomimetic nanocapsules, fabricating functional nanomedicines, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Typical Janus particles were micro-or nano-sized particles composed of two hemispheres with distinct chemical or physical properties. [11][12][13][14][15][16][17] However, the difficulties in synthesizing Janus supramolecular polymers were enormous. 9,10 These unique properties also made Janus-type supramolecular polymers very promising in biomedical applications including mimicking primitive biological membranes, conguring into biomimetic nanocapsules, fabricating functional nanomedicines, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…This class of polymers has the benefit of controlling the design, as well as versatile construction [49][50][51][52][53][54][55]. Consequently, these are promising candidates for light-harvesting systems, drug delivery, storage information, and catalysis [52,56,57].…”
Section: Star and Dendritic Architectures Incorporating Azo Moleculesmentioning
confidence: 99%
“…It has been reported that bis(terpyridine) ruthenium-connected PNIPAM copolymer has good hydrophilic and "smart" thermo-responsive nature to be utilized potentially in polymer supported catalyst applications. 21 Furthermore, once self-assembled, this thermo-responsive nature could be used to enable a change in morphology by shifting the hydrophobic to hydrophilic ration of the building blocks 21 with the above mentioned advantages of metallopolymer and MWCNTs MWCNTs can be easily functionalized by using metallopolymer (RuTpyPNIPAM) to design new kinds of ruthenium-CNT based nonmaterials that combine advantages of both ruthenium metallopolymers and CNTs. Reversible additionfragment chain transfer (RAFT) polymerization has been used for synthesis of the ruthenium ligand of terpyridineended copolymer, since RAFT is accessible to precisely control polymer ligands molecular weight and distributions as well as versatility in monomer selectivity to increase the solubility of ruthenium functionalized MWCNTs (RuMWCNTs).…”
Section: Introductionmentioning
confidence: 99%
“…These may find new potential applications for self-heatable coatings and intelligent memory materials. [21][22][23] Ruthenium terpyridine complexes also have special photochemical and redox properties, which allow for supramolecular self-assembly, design of new functional polymer metal complexes and other applications for luminescent devices or sensitizers. [24][25][26] Because carbon nanotubes are electron acceptors due to their extended -electron conjugation and ruthenium terpyridine complexes have the electron donor properties with metal ion centers, 27 the interaction between CNTs and ruthenium terpyridine complexes relies on electrochemical change in ruthenium redox potential or photophysical switching of the contact between CNTs and ruthenium complexes.…”
Section: Introductionmentioning
confidence: 99%